Analysis of Climate Change from the Aliguodarz Region Farmers’ Viewpoint with an Emphasis on the Central District - Mohammad Tavakoli; Bohlol Alijani; Reza Borna; Hosain Mohammadi (جغرافیا و پایداری محیط)
Agricultural sector is directly affected by climate change, and certainly, the exacerbation of climate anomalies in the future, can threaten the supply of human food. Therefore, the agricultural sector can have the greatest impact on the phenomenon of climate change and also climate change will exacerbate drought and disrupt agricultural activity. Therefore, it is necessary to predict or simulate this effect using various available tools in the field of management, to ensure consumer food security and the maximum welfare of producers, with the necessary planning and policy making. The aim of present study was to investigate the viewpoint of farmers in Aligoudarz (Lorestan province) regarding climate change and the factors affecting it. For this purpose, a descriptive research method was used. The statistical population was Aligoudarz farmers and the sample size was 116, which were selected as random sampling. The questionnaire was used as the main tool for collecting data. Besides, the 30-year weather data were used to check climate change in the area. The results showed that more than 42% of the people have been familiar with the issue of climate change through the media including radio and television, and more than 60% of respondents have a negative attitude toward climate change. This topic was emphasized in more than 14 questions from the questionnaire.